ETNOBOTANY OF TRADITIONAL MEDICINE PLANTS IN THE COMMUNITY OF KADINDI VILLAGE, PEKAT DISTRICT, DOMPU REGENCY - Muliawan, Wawan (Cocos Bio, 2021)
The use of plants as traditional medicine has been known for a long time by the community in Kadindi Village, Pekat District. This traditional medicine is passed down from generation to generation. However, at this time due to the development of times and traditional technology began to be abandoned, therefore it is very important to know again about the knowledge of medicinal plants that are used by the community. This study aims to determine the types of plants used by the people of Kadindi Village, Pekat District, the parts of plants used as medicine and how to use these plants in the treatment of various diseases. The type of research used in this research is descriptive qualitative research and the sampling technique is purposive sampling. Where the data was obtained from the results of direct interviews with the people of Kadindi Village, Pekat District. The amount of information used was 20 respondents from two hamlets in Kadindi Village. Based on the research results, 35 types of medicinal plants were widely used by the people of Kadindi Village in the treatment of various diseases. The parts used are the roots, leaves, seeds, fruit, rhizomes, tubers, skin, air, and seeds. There are various kinds of processing, some are drunk, rubbed on, put on, put into the nostrils, used for shampooing, used for bathing, used for bathing and in thefemale area.